A radiation hybrid map of bovine X Chromosome (BTAX) - Amaral, Maria Elisabete Jorge [UNESP]; Kata, Srinivas R.; Womack, James E. (Springer Nature, 2002)
We present a comprehensive radiation hybrid map of the bovine X chromosome (Chr) containing 20 new markers, including both microsatellites and expressed genes. This study was conducted with a 5000-rad whole genome RH cell panel consisting of 90 hybrid cell lines. Retention frequencies of individual markers range from 7.8% for XIST to 31.1% for TGLA325. Statistical analysis with RHMAPPER placed all the loci into five linkage groups under a LOD score criterion of 6.0. These groups could be oriented relative to each other because they included multiple microsatellite loci from the consensus linkage map of the X Chr. Markers included in both this RH map and the bovine cytogenetic map were in a consistent order. The comparative bovine-human map thus generated consists of five blocks of genes, the order of which is conserved, although in the opposite direction when presented as ideograms with p and q arms. Inversions of three blocks account for the difference in gene order across the entirety of the two X Chrs.
Keywords: cattle; chromosome inversion; chromosome marker; cytogenetics; gene locus; gene order; genetic conservation; genetic linkage; genome; hybrid cell; nonhuman; radiation hybrid mapping; X chromosome; Animals; Cattle; DNA; Genetic Markers; Humans; Polymerase Chain Reaction; Radiation Hybrid Mapping; X Chromosome; Bos taurus; Bovinae; Mammalia